Phytochemicals of Zingiberaceae family exhibit potentiality against SARS-CoV-2 main protease identified by a rational computer-aided drug design. Issue 17 (1st September 2022) - Debnath, Sudhan; Bhaumik, Samhita; Sen, Debanjan; Debnath, Bimal
Abstract: Coronavirus disease 2019 (COVID-19) has created huge social, economic and human health crises globally. Discovery of specific drugs has become a new challenge to the researcher. Structure-based virtual-screening of our in-house databank containing1102 phytochemicals of Zingiberaceae family was performed with main protease(M pro ), a crucial enzyme of SARS-CoV-2. Rigorous docking and ADME study of top-scored twenty hits resulted from VS was performed. Then 100 ns molecular dynamics followed by MMPBSA binding free energy(ΔGbind ) calculation of A280 and KZ133 was also performed. These two hits showed good interactions with crucial amino acid residues of M pro HIS-41 and CYS-145, excellent ADME properties, fair ΔGbind values (> ‒188.03 kj/mol), and average protein-ligand complex RMSD < apo-protein RMSD. Therefore, the seed extracts of Alpinia blepharocalyx and rhizome extracts Kaempferia angustifolia containing A280 and KZ133, respectively, may be useful against COVID-19 after the proper biological screening. These two novel scaffolds could be exploited as potent SARS-CoV-2-M pro inhibitors. Graphical Abstract: UF0001